2020
DOI: 10.20473/mgi.v15i1.60-65
|View full text |Cite
|
Sign up to set email alerts
|

HUBUNGAN JENIS KELAMIN, PERILAKU MEROKOK, AKTIVITAS FISIK DENGAN HIPERTENSI PADA PEGAWAI KANTOR<br><i>[Correlation of Sex, Smoking Habit, Physical Activity and Hypertension among Offi ce Employee]</br></i>

Abstract: Hypertension is known as the silent killer. Hypertension can be caused by non-modifi able factor such as gender and modifi able factor such as smoking habit and physical activity. Purpose of this study was to examine the relationship between gender, smoking habit, and physical activity with hypertension among offi ce employees in Provincial Public Health Offi ce of Central Java. This study used case control design. This case control study included 46 offi ce employee, divided into 23 cases and 23 controls who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 8 publications
2
6
0
9
Order By: Relevance
“…Based on table 1, physical activity varied and was relatively balanced at all levels, even though the level of strenuous activity is the most common. The level of strenuous physical activity did not always mean that the respondents do the type of strenuous activity such as lifting weights and other high-intensity sports 32 . It could mean that there were many of them who did a series of moderate physical activities 33 , such as sweeping and mopping the floor, and washing dishes and clothes repeatedly every week.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Based on table 1, physical activity varied and was relatively balanced at all levels, even though the level of strenuous activity is the most common. The level of strenuous physical activity did not always mean that the respondents do the type of strenuous activity such as lifting weights and other high-intensity sports 32 . It could mean that there were many of them who did a series of moderate physical activities 33 , such as sweeping and mopping the floor, and washing dishes and clothes repeatedly every week.…”
Section: Resultsmentioning
confidence: 94%
“…It could mean that there were many of them who did a series of moderate physical activities 33 , such as sweeping and mopping the floor, and washing dishes and clothes repeatedly every week. Other examples of moderate activity that students did was gardening, dancing and aerobics 32 . The results showed that most of the students were physically active.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rokok mengandung nikotin sebagai penyebab ketagihan dan merangsang pelepasan adrenalin sehingga kerja jantung lebih cepat dan kuat, akhirnya terjadi peningkatan tekanan darah. 14…”
Section: Kebiasaan Merokokunclassified
“…Faktor aktivitas fisik dapat mempengaruhi terhadap tekanan darah karena seseorang yang kurang aktif melakukan aktivitas fisik dapat menyebabkan pembulu darah menjadi tidak elastis atau kaku sehingga aliran darah tidak lancar dan jantung lebih bekerja dalam memompa darah serta menimbulkan tekanan darah tinggi. Menurut Garwahusada & Wirjatmadi (2020) menyatakan bahwa seseorang dengan aktivitas fisik yang baik dan aktif umumnya mempunyai tekanan darah yang lebih rendah dan lebih jarang terkena tekanan darah tinggi dan cenderung untuk mempunyai fungsi otot dan sendi yang lebih baik, karena organ-organ demikian lebih kuat dan lebih lentur. Aktivitas fisik yang berupa gerakan atau latihan aerobik bermanfaat untuk meningkatkan dan mempertahankan kebugaran, ketahanan kardio-respirator.…”
Section: ) Tekanan Darah Lansia Hipertensiunclassified